Assessment of dynamic transformer rating, considering current and temperature limitations; International Journal of Electrical Power & Energy Systems; Vol. 129 - Daminov I. B. Ildar Bolatovich; Prokhorov A. V. Anton Viktorovich; Caire R. Raphael; Alvarez-Herault M.-C. Marie-Cecile (2021, 2021)
Title screen